MINI REVIEW: SINTESIS DAN KARAKTERISASI NANOPARTIKEL ZnO DENGAN METODE PRESIPITASI - Bergita, Angela; Hindryawati, Noor; Hiyahara, Irfan Ashari (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
ZnO nanoparticles are materials composed of particles ranging in size from 1 to 100 nm and can be produced through the precipitation method. This method is highly popular due to its cost-effectiveness. Numerous studies on the synthesis of ZnO nanoparticles using the precipitation method have been conducted. This mini-review aims to explore the characteristics of nanoparticles synthesized using the precipitation method. The approach employed in this journal involves a literature review of several journals focusing on the synthesis of ZnO nanoparticles through precipitation. The synthesis results in ZnO nanoparticles with sizes ranging from 4.38 nm to 1400 nm, possessing a hexagonal wurtzite crystal structure and bandgaps ranging from 3.57 to 3.7943 eV. Based on the conducted review, it can be concluded that the material that yields small-sized nanoparticles with high purity includes the precursor ZnSO4(H2O)7, deionized water as the solvent, and NH4OH as the catalyst. Keywords: Nanoparticles, Precipitation, Zinc Oxide